On-board generation of hydrogen to improve in-cylinder combustion and after-treatment efficiency and emissions performance of a hybrid hydrogen–gasoline engine. (17th May 2019) - Martin, Juan-Carlos; Millington, Paul; Campbell, Bruce; Barron, Luke; Fisher, Stewart
Abstract: Hydrogen on-board fuel reforming has been identified as a waste energy recovery technology with potential to improve Internal combustion engines (ICE) efficiency. Additionally, can help to reduce CO2, NOx and particulate matter (PM) emissions. As this thermochemical energy is recovered from the hot exhaust stream and used in an efficient way by endothermic catalytic reforming of petrol mixed with a fraction of the engine exhaust gas. The hydrogen-rich reformate has higher enthalpy than the petrol fed to the reformer and is recirculated to the intake manifold, which will be called reformed exhaust gas recirculation (rEGR). The rEGR system has been simulated by supplying hydrogen (H2 ) and carbon monoxide (CO) into a conventional Exhaust Gas Recirculation (EGR) system. The hydrogen and CO concentrations in the rEGR stream were selected to be achievable in practice at typical gasoline exhaust temperatures (temperatures between 300 and 600 °C). A special attention has been paid on comparing rEGR to the baseline ICE, and to conventional EGR. The results demonstrate the potential of rEGR to simultaneously increase thermal efficiency, reduce gaseous emissions and decrease PM formation. Complete fuel reformation can increase the calorific value of the fuel by 28%. This energy can be provided by the waste heat in the exhaust and so it is ideal for combination with a gasoline engine with its high engine-out exhaust temperatures. The aim of this work is to demonstrate that exhaust gas fuel reforming on an engine is possible and is commercially viable. Also, this paper demonstrates how the combustion of reformate in a direct injection gasoline engine via reformed Exhaust Gas Recirculation (rEGR) can be beneficial to engine performance and emissions. Highlights: Using rEGR increase the stability of combustion. The use of H2 has demonstrated fuel economy benefit, shown at steady-state. It has been proved that H2 provide an increase in calorific value of reformed fuel. Increase in tolerable rEGR limit, reducing pumping losses. rEGR not only improve the stability of combustion also provide cleaner emissions.